Collection and Preservation of the Sperm Garangan ((Herpestes javanicus) - Alvien Nuraini; Ni Luh Putu Rischa Phadmacanty; Yulianto Yulianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Cryopreservation technique can be used to preserve animal cell, plant, or other genetic materials including frozen semen. Herpestes javanicus is one of wild animals with a large number but no data about the sperm quality and technique how to preserve it. This research is proposed to know sperm quality of H. javanicus and the technique to preserve it. In this research, the three different methods were used to collect sperms. Those methods were electroejaculator, flushing and maceration/cutting, respectively. The sperm was then analyzed for quality, such as: volume, pH, viscosity, colour, smell, motility, concentrasion, viability, morphology and morphometry. Then the sperms were preserved in tris citrate glucose egg yolk extender by different concentrations. The result showed that the best method for collecting sperms was by maceration/cuting method, and the best extender for sperms was low concentration of tris cytrate glucose egg yolk. Keywords: cryopreservation, Herpentes javanicus, sperm quality, preserve method, extender